2007
DOI: 10.1104/pp.107.105882
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Improve K+/Na+ Homeostasis in Barley Seedlings by Regulating Root Ion Channel Activities

Abstract: Polyamines are known to increase in plant cells in response to a variety of stress conditions. However, the physiological roles of elevated polyamines are not understood well. Here we investigated the effects of polyamines on ion channel activities by applying patch-clamp techniques to protoplasts derived from barley (Hordeum vulgare) seedling root cells. Extracellular application of polyamines significantly blocked the inward Na 1 and K 1 currents (especially Na 1 currents) in root epidermal and cortical cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 59 publications
4
89
0
6
Order By: Relevance
“…Inhibition of the inward Na + and K + currents (especially Na + currents) by extracellular PAs (1 mM) has also been reported in barley root epidermal and cortical cells (Zhao et al 2007). Shabala et al (2007) showed that micromolar concentrations of PAs are efficient in preventing NaCl induced K ' -efflux by blocking the nonselective cation channels in mesophyll cells of pea (Pisum sativum L.).…”
Section: Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the inward Na + and K + currents (especially Na + currents) by extracellular PAs (1 mM) has also been reported in barley root epidermal and cortical cells (Zhao et al 2007). Shabala et al (2007) showed that micromolar concentrations of PAs are efficient in preventing NaCl induced K ' -efflux by blocking the nonselective cation channels in mesophyll cells of pea (Pisum sativum L.).…”
Section: Salinitymentioning
confidence: 99%
“…Similarly, exogenous application of PAs (1 mM) significantly blocked the inward Na ' currents in epidermal and cortical cells of barley (Hordeum vulgare) roots. Thus, polyamine-induced repression of Na ' influx into roots and prevention of K ' loss from shoots maintained low [Na ' ]/[K ' ] ratio in barley seedlings and thereby conferring tolerance to salinity (Zhao et al 2007). It has also been reported that PAs including Spm inhibit stomatal opening and induce closure by regulating KAT1-like voltage-dependent inward K ' channels of Vicia faba guard cells (Liu et al 2000).…”
Section: Salinitymentioning
confidence: 99%
“…Moreover, they are implicated in defense responses to various biotic and abiotic stresses (Bouchereau et al, 1999;Walters, 2003;Kusano et al, 2007;Cuevas et al, 2008) and participate in signaling pathways by regulation of cation channel activities (Kusano et al, 2008) such as during stomatal closure (Liu et al, 2000) and salt stress response (Zhao et al, 2007). As concerns root development, it has been reported that exogenously supplied Spd affects cell elongation and shape as well as the mitotic index in maize (Zea mays) primary roots (de Agazio et al, 1995).…”
mentioning
confidence: 99%
“…The increase in polyamine levels may be an integral selfprotecting response to salinity environments (Zhao et al 2007). In a previous study, we generated transgenic tomato lines overexpressing apple spermidine synthase (MdSPDS1, Zhang et al 2003) under the control of 35S promoter (Neily et al 2010).…”
mentioning
confidence: 99%